Protein-Tyrosine Phosphatase 1B (PTP1B): A Novel Therapeutic Target for Type 2 Diabetes Mellitus, Obesity and Related States of Insulin Resistance - Goldstein, B.J. (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2001)
Resistance to the cellular action of insulin, a fundamental pathophysiological defect accompanying the worldwide epidemic of obesity, is closely associated with the development of type 2 diabetes mellitus and the set of cardiovascular risk factors that Constitute the “metabolic” syndrome. The development of novel pharmaceutical agents that help ameliorate insulin resistance will be potentially important not only for the prevention and treatment of diabetes, but also in reducing its associated cardiovascular risk profile. Studies on the cellular role of the protein-tyrosine phosphatase PTP1B have now clearly shown that it serves as a key negative regulator of the tyrosine phosphorylation cascade integral to the insulin signaling pathway. Genetically-modified mice that lack PTP1B protein expression and animals treated with a specific PTP1B antisense oligonucleotide have provided crucial “proof-of-concept” data to show that eradicating or reducing PTP1B enhances insulin signaling and glucose tolerance. PTP1B inhibition also reduces adipose tissue storage of triglyceride under conditions of over-nutrition and was not associated with any obvious toxicity. The effects of the loss of PTP1B in vivo were also remarkably specific for components of the insulin action cascade, in spite of cellular studies suggesting that PTP1B may exert a regulatory influence on a variety of other signaling pathways. Overall, these studies have paved the way for the commercial development of PTP1B inhibitors that may serve as a novel type of “insulin sensitizer” in the management of type 2 diabetes and the cardiovascular / metabolic syndrome.
Keywords: Protein-Tyrosine Phosphatase 1B PTP1B